Galerie Pierre Marie Vitoux 1988-1998. - Arnault-Tran, Martine; Artaud, Evelyne; Galerie Pierre Marie Vitoux, Paris (Paris : Galerie Pierre Marie Vitoux, 1998)
Amblard, Frédéric ; Arickx, Lydie ; Baillon, Agnès ; Bignolais, Gérard ; Crestou, Nicole ; Duprez, Alexandra ; Hadad, Abraham ; Josse, Monique ; Koller, Ben-Ami ; Labegorre, Serge ; Mariknecht ; Mihuleac, Wanda ; Moscovici, Ariel ; Olariu, Iulan ; Picciotto, Simone ; Rauzy, Marie ; Rocher, Maurice ; Rustin, Jean ; De Sagazan, Olivier ; Vermeersch, José
biografie
Frans
boek